2017
DOI: 10.3892/ol.2017.6054
|View full text |Cite
|
Sign up to set email alerts
|

The clinicopathological and prognostic role of thrombocytosis in patients with cancer: A meta-analysis

Abstract: Abstract. Previous studies have linked the presence of thrombocytosis with the progression and development of cancer; however, this trend requires further investigation. The present study aimed to derive an estimation of the degree of association between thrombocytosis and the 5-year overall survival rate of patients with cancer, as well as common clinicopathological features, by performing a meta-analysis of 20 (n=12,778) published studies. The PubMed and Embase databases were searched systematically for all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Paraneoplastic thrombocytosis was driven by IL-6 and hepatic thrombopoietin, both of which stimulated tumor cell proliferation and migration; however, the mechanism is not clearly understood [28]. Previous studies in cancer patients showed that a platelet count > 400,000/mm 3 correlated with advanced stage of disease and decreased 5-year OS (odds ratio = 2.70, 95% CI: 2.03–3.61) [29]. The impact of pretreatment platelet counts in early stage cervical cancer is still being debated [30].…”
Section: Discussionmentioning
confidence: 99%
“…Paraneoplastic thrombocytosis was driven by IL-6 and hepatic thrombopoietin, both of which stimulated tumor cell proliferation and migration; however, the mechanism is not clearly understood [28]. Previous studies in cancer patients showed that a platelet count > 400,000/mm 3 correlated with advanced stage of disease and decreased 5-year OS (odds ratio = 2.70, 95% CI: 2.03–3.61) [29]. The impact of pretreatment platelet counts in early stage cervical cancer is still being debated [30].…”
Section: Discussionmentioning
confidence: 99%
“…Other potential but unproven immune escape mechanisms include platelet-T-cell interactions. Thrombocythemia confers a dismal prognosis in several types of solid malignancies [72]. The thrombocythemia commonly found in MPN patients has been speculated to give rise to increased cancer invasiveness and enhance the metastatic potential of second cancers through a "platelet-cancer loop" [73].…”
Section: Immune-subversive Mechanisms In Mpnmentioning
confidence: 99%
“…Fewer effector T cells in peripheral blood PMF [40] Fewer NK cells in peripheral blood All MPN [43] Elevated numbers of MDSC in peripheral blood All MPN [47,48] Higher inhibitory potential of MDSC in peripheral blood All MPN [47] Elevated TGFβ production by bone-marrow-derived monocytes PMF [57] Lower levels of naïve T-cells and higher levels of terminally differentiated effector T-cells PV [58] Lower levels HLA-I on monocytes PV [58] Lower levels of HLA-I on mutant cells CALR-mutant MPN [72] Deregulation of genes related to antigen processing and activation as well as immune cell activation and inflammation All MPN [59][60][61] Lower number of myeloid dendritic cells and lower priming potential of myeloid dendritic cells Myeloid cells such as monocytes and myeloid-derived suppressor cells secrete TGF-β and ARG1, respectively. These proteins are highly immunosuppressive to T cells and thus induce immune suppression in the tumor microenvironment (TME).…”
Section: Escape Mechanism Mpn Type Referencementioning
confidence: 99%
“… 11 , 12 Previous studies have shown that increased platelet count is associated with poor disease-free survival (DFS) and overall survival of various cancers. 13 , 15 However, the prognostic value of the platelet count for locally advanced breast cancer patients with ISLN metastasis is rarely reported. The purpose of this study is to explore the prognostic value of peripheral blood platelet count in breast cancer patients with ISLN metastasis.…”
Section: Introductionmentioning
confidence: 99%